PENDIDIKAN ISLAM DALAM PERSPEKTIF ZAKIYAH DARAJAT TENTANG CATUR PUSAT PENDIDIKAN ISLAM - Andy Takwin Fitriansyah; Maskuri Bakri; Moh. Eko Nasrullah (VICRATINA, 2022)
Problems in education that occur in life, so that they experience a moral decline and an identity crisis in children. This is where it is explained how the importance of Islamic education is contained in the family aspect, school aspect and community aspect so that Islamic education becomes the central chess in education. In order to be able to answer the research objectives above, this research uses library research, so that with this method, various literature sources related to the subject matter discussed regarding Maskur Bakri's views on character education are examined. Based on the results of the studies that have been discussed in this thesis, after the researchers conducted research on the thoughts of Prof. Dr. Zakiah Daradjat on Islamic education: a study of environmental aspects of Islamic education. The concept of Islamic education for Zakiah Daradjat is first: it includes all human dimensions. Second: reach the life of the world and  the  hereafter  in  a balanced  way.  Third:  pay  attention  to  humans  in  all  their movements, and develop in them the power of relationships with other people. Fourth: Islamic education lasts a lifetime. Fifth: Islamic education produces human beings who have rights in this world and rights in the hereafter.